Induced expression of miR‐1250‐5p exerts tumor suppressive role in triple‐negative breast cancer cells. Issue 2 (22nd December 2022) - Shuaib, Mohd; Kumar, Shashank
Abstract: Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer, and it has a prevalence rate of 15%–20% among all breast cancer cases in younger women. Still, the underlying molecular mechanisms of its pathogenesis are not entirely understood. In the previous study, we identified that microRNA (miR)‐1250‐5p is significantly down‐expressed in TNBC cells. Thus, in the present study, we explore the functional anticancer role of miR‑1250‑5p in the transient mimic transfected TNBC cells. 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2H‐tetrazolium bromide (MTT) assay was used to examine the effect of miR‐1250‐5p on cell viability of TNBC (MDA‐MB‐231 and MDA‐MB‐453) cells. The confocal microscopy, quantitative real‐time polymerase chain reaction, and western blot analysis techniques were used to assess the effect of miR‐1250‐5p on cancer hallmarks in test cells. Induced miR‑1250‐5p expression in MDA‐MB‐231 and MDA‐MB‐453 cells decreased cell viability in a time‐dependent manner. Increased miR‑1250‐5p expression levels significantly decreased cell cycle G1/S phase transition markers (Cyclin D1 and CDK4) at messenger RNA (mRNA) and protein levels in TNBC cells compared to scrambled sequence transfected cells. Transient transfection of TNBC cells with miR‐1250‐5p mimic increased apoptosis in TNBC cells by increasing the level of active caspase (Caspase 8 and Caspase 3) of the intrinsic pathway. Apoptosis‐related morphological changes were also observed in the test cells. Further, the induced expression of miR‐1250‐5p significantly decreased epithelial‐mesenchymal transition (EMT) by altering the mRNA and protein levels of E‐cadherin and Vimentin. Moreover, results of confocal microscopy revealed increased reactive oxygen species generation, and decreased mitochondria membrane potential in miR‐1250‐5p mimic transient transfected TNBC cells. In conclusion, miR‑1250‐5p acts as tumor suppressor in TNBC cells and its induction by therapeutics might be a novel strategy for the disease treatment.